RECOGNISING THE INFLUENCE OF INTER-PROFESSIONAL RELATIONS ON END OF LIFE CARE TRANSITIONS: VIEWS OF BEREAVED CARERS AND PROFESSIONALS. Issue 1 (1st March 2013) - Valtorta, N; Hanratty, B; Lowson, E; Grande, G; Addington-Hall, J; Seymour, J; Payne, S
Abstract : Introduction: The end-of-life care needs of older adults with multiple conditions are complex and involve a range of professionals working in different settings. This study focuses on transitions, as vulnerable points in care pathways experienced by a high proportion of the older population at the end of life. Aims and Methods: To understand how inter-professional relations influence transitions between settings for older adults at the end of life. Methods: In-depth qualitative interviews with 118 caregivers of decedents aged 66–98 years, who had died with heart failure, chronic obstructive pulmonary disease, stroke, selected cancers; 43 providers and commissioners of services in primary care, hospital, hospice, social care and ambulance services in England. Results: Carers regretted that communication and handovers between professionals did not always take place where they felt them to be necessary, and perceived frequent, repeated assessments and interventions to be the consequence. Families felt compelled to take responsibility themselves and fill gaps left by deficiencies in inter-professional communication and working. Professionals described stereotypical divisions between health and social care, with differences in culture, language and approaches to patients or clients. The dominance of the medical model in end of life care was perceived to be unhelpful in creating close working relationships between health and social care. The impact of inter-professional tensions on patients and families went unacknowledged by staff. Conclusions: Inter-professional relationships are an important influence on patient and family experiences of end of life care. It may be an overlooked source of inequity.